Wireless Sensor material Fusion based Single photon indium phosphide on silicon chip for frequency-modulated continuous-wave light detection and ranging. Issue 1 (February 2021) - Selvakumar, R; Singh, Ngangbam Phalguni; Suman, Shruti
Abstract: Enormous of improvement happing in the Autonomous Vehicle Navigation Sector (AVNS), Especially in Wireless Sensory devices manufacturing materials based investigation and deployment present hotspot research. We investigated various semiconductors materials and proposing Single Photon (SP) driven silicon chip for autonomous System (AS). We also proposed an Indium Phosphide (InP) material composite design and optimization to improve the photon mobility, conductivity and frequency. Material used for fabrication of autonomous system performance is directly propositional in the following factors: thermal stability in various refractive index (nD) The proposed material InP integrated with the white phosphorus reaction with indium iodide at 250 °C, it induces the direct band gap 1.33 eV (600 and speed of electron moments scattered in all the areas. To make it intense path instead of electron we introduced single photon indium phosphide (SPInP) on silicon chip (SoC) adding with photonic integrated circuits (PICs). In this method wavelength sensitivity improved single to three pulse range various from 905 nm to 1480 nm compound attenuation reaches to 0.3833 dB/Km. Signal and detection and conversion SPInP SoC more suitably in Frequency Modulated Continuous Wave (FMCW) coherent based Light Detection and Ranging (LiDAR) integrated with Indium Phosphide photomultipliers (InPPMs) theory parameter analysis, optimized Angle of Arrival (AoA), less signal error, power ratio, distance, velocity, error detection in frequency domain and simulation desired characteristics are presented.